The Use of Humor Stories in Teaching Reading Comprehension to Students of Mts Negeri 1 Sidrap - Hudzaifa Afifah Hamka; A. Muliati; Amra Ariyani (Journal of Excellence in English Language Education, 2022)
The objective of this research was to find out whether or not the use of humor stories in teaching reading improves students’ reading comprehension. This research took place at MTs Negeri 1 Sidrap. The population of this research was the third-grade students of MTs Negeri 1 Sidrap. The researchers used cluster random sampling technique in selecting samples. These researchers used pre-experimental design. The instrument of this research was a reading test which administered as a pretest and posttest. Based on the result of mean score, the researchers found that the use of humor stories in teaching reading comprehension improves because it was found that the post-test score is higher than the pre-test (78.2 > 85.0). So, it can be concluded that the use of humor stories improves students reading at MTs Negeri 1 Sidrap academic year 2021/2022.